Problematika Penggunaan Website Learning SIMPeL 12 Terhadap Hasil Belajar Geografi di SMA Negeri 12 Semarang Tahun Ajaran 2020/2021 (Jurusan Geografi, Fakultas Ilmu Sosial, Universitas Negeri Semarang, 2022)
SIMPeL 12 as website learning was used at SMA Negeri 12 Semarang. The aims of thus study are: (1) To find out the problems of using the SIMPeL 12 learning website in geography subjects at SMA Negeri 12 Semarang. (2) Know the result of studying geography at SMA Negeri 12 Semarang. (3) Determine the effect of problematic use of the SIMPeL 12 learning website on the learning outcomes of geography at SMA Negeri 12 Semarang. The method used in this research is descriptive quantitative with data collection using questionnaires, interviews, and documentation. The analysis technique used is descriptive statistics and simple regression. The result of this study indicate that (1) the problems of using the SIMPeL 12 learning website in geography subject get an average criterion of “High” with a percentage of 68,1%, caused by internal factors consisting of interest and readiness, motivation, and family. While external factors consist of access and flexibility, facilities and infrastructure, cost, and geography subject matter. (2) the result of the study of geography showed that as many as 42 samples did not reach the Minimum Completeness Criteria. (3) the effect of the problematic use of the SIMPeL 12 learning website on the learning outcomes of geography at SMA Negeri 12 Semarang is 25%.